Penerapan Pembelajaran Lapangan Melalui Kampus Mengajar Angkatan 3 di UPT SD Negeri 81 Kalukubodo Kabupaten Takalar - Asrul; Alam, Sahrul; Moh Ahsan S Mandra; Arham; Andika; Nurfadillah; Ramdani (Jurnal Mitra Pengabdian Farmasi, 2023)
Education is a system created and developed to create superior Human Resources to strengthen the nation's competitiveness. But in its development there are various problems, one of which is the uneven distribution of facilities and infrastructure, the application of learning methods and models that are not in accordance with the times and the participation of the community and all stakeholders have not optimally contributed to the development of the education system in Indonesia. The Teaching Campus Program batch 3 is one of the MBKM activities which is a solution to address various educational problems in Indonesia, especially education at the Elementary School level and Junior High School education units. Apart from that, campus teaching is also a form of empowering students to gain field learning and at the same time a form of real contribution as an Agent of Change in the world of education, as well as a forum for the development of student Soft Skills and Hard Skills. The results obtained in the implementation of KM 3 are: (1) has provided training on the adaptation and application of learning technology to teachers and students, (2) the application of learning methods and models that are in accordance with the times, (3) the application of learning that is oriented towards increasing literacy and student numeracy, (4) assisting teachers in school administration and (5) there is an increase in literacy, numeracy, student motivation and the ability to adapt technology by teachers and students.